Assessment of Demographic and Socio-Behavioral Factors on Adherence to HIV Pre-Exposure Prophylaxis Using a Markov Modeling Approach - Mallayasamy, Surulivelrajan; Chaturvedula, Ayyappa; Fossler, Michael J.; Sale, Mark E.; Hendrix, Craig W.; Haberer, Jessica E. (Frontiers in Pharmacology, 2019)
Purpose: Adherence is important for the effectiveness of HIV pre-exposure prophylaxis (PrEP). Our objective is to assess the impact of multiple demographic and socio-behavioral factors on the adherence to tenofovir-based PrEP among HIV serodiscordant couples using a Markov mixed effects modeling approach. Methods: The Partners Demonstration Project was a prospective, open label study of PrEP among heterosexual serodiscordant couples in Kenya and Uganda. The uninfected partner received oral PrEP according to the “bridge to ART” strategy (i.e., until the infected partner took antiretroviral therapy [ART] for >6 months). Adherence was monitored electronically; demographic and socio-behavioral data were collected during study visits. Analyzed data reflect 12 months of follow-up per participant. A two-state, first order, discrete time Markov model was developed with longitudinal adherence data characterized by “dose-taking (1)” and “dose-missing (0)”. Covariate effects were linearly added in the logit domain of transition probability parameters (P01 and P10) in the model. The full covariate model was initially developed, followed by backward elimination process to reduce the model. All significant covariates reported by a prior primary statistical analysis of the same data were included in the full covariate model. Results: The model included data from 920 participants. Significant covariates associated with higher adherence were age >25 years (odds ratio [OR] for P10, 0.61), female gender (OR for P10, 0.67), participant wanting the relationship with the partner to succeed (OR for P10, 0.79; OR for P01, 1.45), and sex with partner either with 100% or <100% condom use compared to those who reported no sex (OR for P10, 0.84; OR for P01, 1.21). Significant covariates associated with lower adherence were partner on ART >6 months (OR for P01, 0.86; OR for P10, 1.34), subject in the study for >6 months (OR for P01, 0.8; OR for P10, 1.25), and problematic alcohol use (OR for P01, 0.63; OR for P10, 1.16). Conclusion: The developed Markov model provides a mechanistic understanding of relationship between demographic, socio-behavioral covariates and PrEP adherence, by indicating the pattern of adherence influenced by each factor over time. Such data can be used to further intervention development to promote PrEP adherence.